Neuromimesis: Picturing the Humanities Picturing the Brain - Reilly, Cate (Frontiers in Integrative Neuroscience, 2022)
What do neuroscientific visualizations of mental functioning depict? This paper argues that neuroscientific imaging from Santiago Ramón y Cajal’s pen and ink drawings onward falls within the mimetic tradition, that dealing with the artistic representation of reality. Cajal’s iconic images of pyramidal neurons and glial cells surprisingly suggest a non-realist approach to picturing the brain, and so too the mind, that opens a new methodological link between the humanities and neurosciences. In it, aesthetic works offer a perspective on mimetic practices in the neurosciences, providing insight into the representational strategies that make otherwise invisible psychic phenomena observable. This approach draws needed attention to the role of metaphor in neuroscientific research. It also reimagines how interdisciplinary scholarship might engage with works of art. While it is common practice to read humanities objects featuring the brain and/or mind in terms of their neuroscientific content, films like The Headless Woman (La mujer sin cabeza, dir. Lucretia Martel, 2008), explored here, show that doing so can easily inhibit interpretations with greater explanatory bearing. Together, Cajal’s images and Martel’s film help elaborate a fresh methodological paradigm – distinct from that of neuropsychoanalysis – that situates aesthetic objects as a long-neglected tool in the study of the brain by virtue of (not despite) their imaginative investments.